2009
DOI: 10.5194/bg-6-1361-2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diurnal warming on soil respiration are not equal to the summed effects of day and night warming in a temperate steppe

Abstract: Abstract. The magnitude of daily minimum temperature increase is greater than that of daily maximum temperature increase under climate warming. This study was conducted to examine whether changes in soil respiration under diurnal warming are equal to the summed changes under day and night warming in a temperate steppe in northern China. A full factorial design with day and night warming was used in this study, including control, day (06:00 a.m.-06:00 p.m., local time) warming, night (06:00 p.m.-06:00 a.m.) war… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 53 publications
(63 reference statements)
3
52
3
2
Order By: Relevance
“…A large amount of field experiments still treat it as negligible, although a few experiments have introduced this in their experiment design (Xia et al, 2009;Reich et al, 2006). Through this study, the multi-factor interaction was recognized playing an important role in contributing to terrestrial N 2 O flux (Sect.…”
Section: Interactions Among Multiple Factorsmentioning
confidence: 96%
“…A large amount of field experiments still treat it as negligible, although a few experiments have introduced this in their experiment design (Xia et al, 2009;Reich et al, 2006). Through this study, the multi-factor interaction was recognized playing an important role in contributing to terrestrial N 2 O flux (Sect.…”
Section: Interactions Among Multiple Factorsmentioning
confidence: 96%
“…The warming treatment commenced on 23 April 2006. The detailed description of warming treatment can be found in previous publications Xia et al, 2009). …”
Section: Experimental Designmentioning
confidence: 99%
“…Climate warming is expected to result in unequal changes in daily minimum and maximum temperatures, with the greater trends of night warming than day warming (Eastering et al, 1997;Alward et al, 1999;Zhou et al, 2007). It has been reported that increased daily minimum and maximum temperatures have different effects on biomass and yield (Dhakhwa et al, 1998;Alward et al, 1999;Peng et al, 2004;Lobell, 2007;Lobell and OrtizMonasterio, 2007) as well as C cycling Xia et al, 2009) in terrestrial ecosystems. However, it remains unclear whether asymmetrical warming may have different effects on root growth, mortality and turnover, which plays critical roles in regulating nutrient and C cycling between above-and belowground.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the kinetic parameters of various soil C pools should be fitted to the observational data to determine the temperature sensitivity of the C mineralization, including the rate constants and the relative sizes of the C pools of varying decomposability (Davidson and Janssens, 2006). Furthermore, the temperature sensitivity of C mineralization not only varies in those kinetic properties, which are partially determined by soil properties , but also changes with environmental conditions, such as constant vs. varying temperature regimes (Conant et al, 2008;Fang et al, 2005;Nakajima et al, 2016;Xia et al, 2009;Zhu and Cheng, 2011), the aeration statuses (Blagodatskaya et al, 2014;Devêvre and Horwáth, 2000;Diakova et al, 2016), the forest stands (Guo et al, 2016;Gutiérrez-Girón et al, 2015;Rey and Jarvis, 2006), and the soil horizons (Laganière et al, 2015;Xu et al, 2014). These constraints, especially the temperature and the aeration status, are fixed as constant in most studies, and a continuously changing vs. constant environmental comparison has rarely been scrutinized (Conant et al, 2008;Hartley et al, 2008;Pettersson and Bååth, 2003;Ranneklev and Bååth, 2001).…”
Section: Introductionmentioning
confidence: 99%